A transgenic Alx4‐CreER mouse to analyze anterior limb and nephric duct development. Issue 9 (23rd March 2021) - Rockwell, Devan M.; O'Connor, Amber K.; Bentley‐Ford, Melissa R.; Haycraft, Courtney J.; Croyle, Mandy J.; Brewer, Kathryn M.; Berbari, Nicolas F.; Kesterson, Robert A.; Yoder, Bradley K.
Abstract: Background: Genetic tools to study gene function and the fate of cells in the anterior limb bud are very limited. Results: We describe a transgenic mouse line expressing CreER T2 from the Aristaless‐like 4 ( Alx4 ) promoter that induces recombination in the anterior limb. Cre induction at embryonic day 8.5 revealed that Alx4‐CreER T2 labeled cells using the mTmG Cre reporter contributed to anterior digits I to III as well as the radius of the forelimb. Cre activity is expanded further along the AP axis in the hindlimb than in the forelimb resulting in some Cre reporter cells contributing to digit IV. Induction at later time points labeled cells that become progressively restricted to more anterior digits and proximal structures. Comparison of Cre expression from the Alx4 promoter transgene with endogenous Alx4 expression reveals Cre expression is slightly expanded posteriorly relative to the endogenous Alx4 expression. Using Alx4‐CreER T2 to induce loss of intraflagellar transport 88 ( Ift88 ), a gene required for ciliogenesis, hedgehog signaling, and limb patterning, did not cause overt skeletal malformations. However, the efficiency of deletion, time needed for Ift88 protein turnover, and for cilia to regress may hinder using this approach to analyze cilia in the limb. Alx4‐CreER T2 is also active in the mesonephros and nephric duct that contribute to the collecting tubules and ducts of the adult nephron. Embryonic activation of the Alx4‐CreER T2 in the Ift88 conditional line results in cyst formation in the collecting tubules/ducts. Conclusion: Overall, the Alx4‐CreER T2 line will be a new tool to assess cell fates and analyze gene function in the anterior limb, mesonephros, and nephric duct. Key Findings: Development of a new inducible Cre line that has activity on the anterior side of the limb bud and nephric tubule. Fate mapping of the anterior cells during limb bud morphogenesis.